KINERJA PEMASARAN : ORIENTASI PASAR DAN INOVASI PRODUK HOME INDUSTRI KERAJINAN SENI UKIR PATUNG MOJOKERTO - Roy Wahyuningsih (STKIP PGRI Jombang, 2022)
This study aims to determine the effect of market orientation and product innovation on marketing performance partially and simultaneously. The population in this study is the home owner of the sculpture carving craft industry in Trowulan District, Mojokerto Regency and the sample taken is 51 respondents obtained by calculating the slovin formula. And as described in the marketing and strategic management literature; that market orientation has a positive impact on marketing performance in a small industry as well as a large company. The results of this study have a positive influence on the significance of market orientation and product innovation on marketing performance. Thus, Market Orientation (X1) and Product Innovation (X2) have an effect on Marketing Performance (Y) in the Home Industry of Sculpture Crafts in Trowulan District, Mojokerto Regency.